Use of 24 h Esophageal pH Monitoring to Demonstrate Alkaline Reflux as a Complication of Gastric Bypass Surgery - J Patrick Shoenut; Rudy G Danzinger (Canadian Journal of Gastroenterology)
A 35-year-old female who had previously undergone a gastric stapling procedure for morbid obesity presented with a persistent nocturnal cough that was treated over a three-year period as a gastric acid reflux complication of the bypass surgery. A barium swallow demonstrated gastroesophageal reflux, but the symptoms did not resolve after treatment with omeprazole and cisapride. Twenty-four hour esophageal pH monitoring subsequently found alkaline reflux in excess of 17% of the total time, with no acid reflux demonstrated. Surgical revision of the bypass Leaving the hiatus alone corrected the reflux complication and the symptoms resolved without further treatment. The diagnostic capability of pH monitoring is illustrated in a patient with an unusual surgical complication.